Contribution of engineer of ways of communication P. Melnikov in planning and building of the first railways of the Russian empire - Dovganyk, S. S. (History of science and technology, 2015)
In the article is illuminated contribution of the first minister of ways of communication of the Russian empire P. Melnikov in planning and building of the first railways of country. The questions of width of track, amount of main tracks, maximum slope, placing of separate points, are examined, technical and economical compare of variants of the designed railways and others.